Achieving Sustainable Performance in the Hospitality Industry based on Environmental Management, Pro-Environmental Behavior and Green Marketing Mix 7P - Rainanto, Bambang Hengky (JDM (Jurnal Dinamika Manajemen), 2023)
The tourism sector is an important sector because it can grow a country’s economy through foreign exchange. However, if not managed properly, tourism can also have negative impacts. This research was located in East Java Province, Indonesia with 228 respondents at the Hotel Manager level. This research aims to develop a relationship model between the Environmental Management System (EMS), Pro-Environmental Behavior (PEB), and the Green Marketing Mix (GMM) as a mediator to achieve Sustainable Industrial Performance (SIP) with 17 hypotheses. Using quantitative methods through surveys and processing using SmartPLS 3. The research results stated that 14 hypotheses were accepted, but 3 hypotheses were rejected. The research results show that the implementation of EMS has a significant relationship with economic and social performance but has no relationship with environmental performance. PEB directly has a significant relationship with environmental performance but not with economic and social performance. GMM has a significant relationship with the three elements of SIP. GMM is also a suitable partial mediator for EMS and PEB to achieve SIP.